A way forward for culturing Plasmodium vivax - Gunalan, Karthigayan (Trends Parasitol, 2020)
Trager and Jensen established a method for culturing Plasmodium falciparum, a breakthrough for malaria research worldwide. Since then, multiple attempts to establish P. vivax in continuous culture have failed. Unlike P. falciparum that can invade all aged erythrocytes, P. vivax is restricted to reticulocytes. Thus, a constant supply of reticulocytes is considered critical for continuous P. vivax growth In vitro. A critical question remains why P. vivax selectively invades reticulocytes? What do reticulocytes offer to P. vivax that is not present in mature erythrocytes? One possibility is the protection from oxidative stress by glucose-6-phosphate dehydrogenase. Here we also suggest supplements to the media and procedures that may reduce oxidative stress and as a result establish a system for continuous culture of P. vivax.